Language learning strategies of successful EFL learners - Sri Mulyani (International Journal in Applied Linguistics of Parahikma, 2020)
This study aimed at exploring language learning strategies applied by successful EFL learners, specifically in learning language elements: vocabulary, pronunciation, and grammar. This study employed qualitative design, involving three participants identified as successful EFL learners. Data were collected through in-depth interviews and document examinations. Miles and Huberman’s model was used as the technique of data analysis. The research findings demonstrated that successful EFL learners in this study employed cognitive, memory, and compensation strategies in learning vocabulary. In learning pronunciation, cognitive and metacognitive strategies were utilized. Meanwhile, in learning grammar, EFL successful learners used cognitive and social strategies. Cognitive strategies were the most frequent strategies used by the participants, while memory, metacognitive, and compensation strategies were the least.